Method and Compounds for Treating Diabetes and Associated Metabolic Diseases (2021)
The disclosure provides for compounds, compositions, and methods of use thereof for treating diabetes (e.g., type 1 diabetes, type 2 diabetes). In some aspects, methods comprise administering first, second, third, fourth, and fifth daily doses of insulin-like growth factor 2 ("IGF-2") or a variant thereof to the subject at respective first, second, third, fourth, and fifth different times, wherein each of the daily doses comprises at least 65 μg of IGF-2. In other aspects, compounds, compositions, and methods containing IGF-2 or variants thereof are used for treating a disorder in a patient in need thereof, such as type 1 or type 2 diabetes.